PWE-148 Long Term Outcomes Of Percutaneous Recanalisation For Budd-chiari Syndrome (bcs): Our Experience In Birmingham, Uk. (9th June 2014) - Sunder Raj, L; Vemala, V; Mangat, K; Olliff, S; Elias, E; Tripathi, D
Abstract : Introduction: Patients with BCS and short stenosis of the hepatic vein or the upper IVC can be treated with recanalisation by percutaneous venoplasty ± hepatic vein stent insertion. Recent data suggests >60% failure rate (PMID 23389867). We studied the long-term outcomes of this approach in our institution. Methods: Retrospective analysis of patients referred from 1987 to 12/2012 for radiological intervention. Of 161 patients treated for BCS, 60 patients were selected. Results: Median age, 34.5 years (19–65), M:F ratio 23:37. Mean follow up, 8 ± 6.6 years (0.1–26 years). 60% of patients had ≥1 haematological risk factor. Percutaneous recanalisation was technically successful in all patients. The obstruction was at the level of hepatic vein (s) (86.6%), IVC (6.6%) and both IVC and HV (6.6%). 30 patients were managed with venoplasty alone. Of the 30 who had stent placement, 15 had venoplasty prior to stent placements, ranging from 1–11 venoplasty episodes. Due to failure of recanalisation, 26.66% patients required TIPSS (16.7%), surgery (8.3%) and liver transplantation (6.7%). Actuarial survival at 1, 5, 10 was 95%, 93%, and 83% respectively ( kaplan meier survival Graph 1 ) . All patients maintained Child's A status throughout follow up and there was no incidence of Hepatocellular Carcinoma. Conclusion: BCS patients due to short stenosis of the hepatic vein or the upper IVC can be successfully managed with percutaneous recanalisation alone with good outcomes over a long period of follow up. Our data supports the stepwise approach to the managements of BCS, with better results than recent series. Reference: PMID 23389867. Good long-term outcome of Budd-Chiari syndrome with a step-wise management. Hepatology 2013 May;57(5):1962–8. doi: 10.1002/hep.26306. Disclosure of Interest: None Declared.